THE MULTI-CULTURAL EXPRESSION OF VISUAL RHETORIC IN FOOD PACKAGING - Farrah Hanani Ahmad Fauzi; Lili Eliana Mohd Radzuan; Fazlina Jaafar; Azian Mohd Zain (International Journal of Accounting, Finance and Business, 2022)
Packaging is able to play an important role in promoting racial integration in Malaysian. The cultural element design is abundantly visible and often ignored by us. A mixed method approach was employed through this study which is the quantitative and qualitative methods. Visual analysis was conducted to analyse visual rhetoric towards two food packaging design. The survey was carried out 30 respondents as data collection. From the findings, illustration such as graphic, pattern or photography was indicated as the main design element that contributed towards culture expression. Finally, it can be concluded that majority of the respondents prefer social and cultural norms characteristics elements implement into packaging design. Identification of the visual rhetoric elements are important to express cultural values. New guidance have been introduced to adopting the best visual rhetoric predominantly cultural expressions on the food packaging design that embrace Malaysians culture.